Aplikasi Pengukuran Penggunaan Prebiotik untuk Tanaman Jagung di Kabupaten Aceh Utara Menggunakan Metode Fuzzy Tsukamoto Berbasis Web - Angga Pratama; Maulida Hasbi; Ananda Faridhatul Ulva (Jurnal Ilmiah SINUS, 2023)
Corn, along with rice and wheat, is one of the world's most significant food crops. Crop failures are a common concern for farmers, and one of the causes is the use of unsuitable fertilizers, which can limit the growth of organs and plant structure as a whole. Because good corn plant growth and high yields require the use of good and appropriate fertilizer for corn plants, this system is designed to recommend fertilization for plants based on the variables required by plants, namely soil pH, air temperature, humidity, rainfall, rainy days, altitude area, solar radiation, and land area, as determined by the agricultural service. Where each value is calculated using a specified set of each criterion, namely little, medium, and high. The outcomes of these computations are the final result of this decision system, namely suggestions for fertilizer usage in liters to assist farmers in analyzing fertilizer use for corn plants in North Aceh District. As in prior works, Tsukamoto's fuzzy technique is applied in this decision-making system to handle data values with a very high level of uncertainty or ambiguity.